Por uma janela aberta: pulsão poética e tradução na obra de Ana Cristina César - Maria Imacula Angelica Nascimento (2015)
Ana Cristina Cesar (1952-1983), writer substantially driven by the need to write, sought in own writing and in the translation work in a poetic warp prevented, with a dense plot that his words could be slithered in pure metaphorical games. In conjunction of this assumption with Freud's concept of 'Drive', whose strength prints a constant impact on the lives of human beings, the reflection proposed here understands that poetic creation itself, in some cases, seem to show insufficient, leading the writer to search add-on creative translation. Reading the life and work of this poet, in this view, it points to a melancholy existence moved by a confrontation with two opposing forces, the 'Drive' and what Blanchot called 'Persecutory hold' - one that prompted the writing and another that tried to stop it, which will lead us to establish analogy between 'Death drive' and 'Persecutory hold'. To understand the meaning reached by translations of Ana Cristina and his method, although this is not privileged in this work, we will use the contemporary theories, especially the Henri Meschonnic in his 'Poética do traduzir'. The purpose of this thesis also involves a dialogue between the work of Ana Cristina Cesar, Sor Juana Inés de la Cruz (1651-1695) and Henriqueta Lisboa (1901-1985).